USM HAS NEVER OFFERED DIPLOMA PROGRAMME IN CUPPING - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
Universiti Sains Malaysia (USM) has never offered any academic programme in cupping at the diploma level. It was believed that certain irresponsible parties had claimed that the university offered such a programme, and the claims had recently gone viral in the social media.